2022
DOI: 10.1101/2022.04.17.488473
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gene editing is suitable to treat GM1 Gangliosidosis: a proof-of-concept study

Abstract: Ganglioside-monosialic acid (GM1) gangliosidosis, a rare autosomal recessive disorder, is frequently caused by deleterious single nucleotide variants (SNVs) in GLB1 gene. These variants result in reduced beta-galactosidase (β-gal) activity, leading to neurodegeneration associated with premature death. Currently, no effective therapy for GM1 gangliosidosis is available. Three ongoing clinical trials aim to deliver a functional copy of the GLB1 gene to stop disease progression. Here, we show that 41% of GLB1 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
(71 reference statements)
0
1
0
Order By: Relevance
“…One of the important methods in delivering therapeutic components is choosing the right type of vector. According to the previous studies of researchers, it can be found that different viral vectors such as lentiviruses, 95,[102][103][104] retroviruses, 105 adenoviruses, 77 and AAVs can be used for gene therapy of GM1 gangliosidosis disease.…”
Section: Pros and Cons Of Therapeutic Vectors And Limitations Of Gene...mentioning
confidence: 99%
“…One of the important methods in delivering therapeutic components is choosing the right type of vector. According to the previous studies of researchers, it can be found that different viral vectors such as lentiviruses, 95,[102][103][104] retroviruses, 105 adenoviruses, 77 and AAVs can be used for gene therapy of GM1 gangliosidosis disease.…”
Section: Pros and Cons Of Therapeutic Vectors And Limitations Of Gene...mentioning
confidence: 99%